Суточная и сезонная активность подземной полевки (Microtus subterraneus Selys-Longch.) в высокогорье Украинских Карпат - Пилявский, Б.Р. (Вестник зоологии, 1970)
The article deals with the materials on diurnal and seasonal activity of Microtus subterraneus in high mountains of the Carpathians.
The periods are established of its highest activity during a day in summer-autumn period of 1962—1963. At the beginning of summer (June —July) Microtus subterraneus are the most active two times a day — in the morning (from 6 to 9 a. m.) and in the Evening (from 5 to 8 p. m.); at the end of summer (August)—three times a day — in the morning (from 4 to 6 a.m ), in the evening (from 9 to 11 p. m.) and at night (from midnight to 3 a. m.); in September — twice a day again: in the morning (from 5 to 11 a. m.) and in the evening (from 4 to 9 p m.).